A solitary papillary lesion on hard palate - Atarbashi-Moghadam, Saede; Mohammadalizadeh chafjiri, Maryam; Moslemi, Hamidreza; Arefifard, Hamidreza; Hassanizadeh, Raheleh (Regeneration, Reconstruction & Restoration (Triple R), 2025)
Oral verruciform xanthoma is an uncommon papillary lesion that is often not taken into consoderation in differential diagnosis of oral papillary lesions. The current case is a solitary papillary lesion on right hard palate of a 33-year-old male with no histroy of swelling or pain. Clinical, histopathologic and immunohistochemical findings of the case is presented and briefly discussed. The aim of the current case report is to attract the clinicians’ attention to uncommon lesions such as verruciform xanthoma.